The Philosophy of Thiruvalluvar and the doctrine of God - P, Praburam (Indian Journal of Tamil, 2026)
By understanding the context of the Thirukkural and the philosophy of God, one can grasp the principles that the author of the text attempts to convey. If one approaches the Thirukkural merely as a book of ethics, which speaks of moral values applicable to all parties, the deeper underlying meanings of the text cannot be uncovered. Therefore, this article explores the notion that the author, Thiruvalluvar, created the Kural against a backdrop of specific religious influences.